Expanding of occidental food companies towar the oriental markets: internationalisations of H3 company in Dubai market case study - Razouk, Majed (2022)
In recent years, there has been increasing globalization and competitiveness of fast food companies. The continued growth and prosperity of these types of companies, brought the challenge of internationalization, also leading to the inherent consideration of cultural considerations to reflect local traditions and cultural diversity of societies and markets. In this framework, European food companies that were primarily focused on local customers and did not directly profit from the strong growth in demand outside the European Union began to expand into international markets, especially to the rich Middle East region, to compete with American and Asian food companies’ dominance there. The United Arab Emirates (UAE), with its oil wealth and diverse economy, is the best area in the Middle East for doing business since expatriates account for two-thirds of the population, and thousands of foreign companies are based there. The H3 Hamburger company is a famous Portuguese brand that started its business in Portugal and spread to other countries like Spain, Brazil, and Poland. Now it prepares to go global and to challenge the big players in both malls and street restaurants virtually everywhere. The purpose of this research is to study the famous and rich Dubai market in an attempt to internationalize the h3™ brand and cross it to the Arab world and to present it as a competitor to hamburger restaurants there. A qualitative and quantitative analysis approach was used to collect data. The qualitative research was performed using cross-communication with people who work and live in Dubai (through online interviews), to accurately understand consumer’s behavior and preferences. The quantitative research was performed using an online survey, to test the conceptual framework of the ancestors and the results of consumer participation in society. To ensure the accuracy of the results, the survey was published in Arabic, which is the official and national language of the UAE. The internationalization strategy used for the case of Dubai steers the course of the company into its international expansion in the Middle East based on its identity, in addition to enhancing competitive advantages, so that the H3 company can find its growth and sustainability. Finally, this study helps new Western brand managers expand and succeed in the UAE.